A multidimensional measure of wellbeing among youth: a cross-sectional study of the Palestinian refugee youth in Lebanon. (July 2021) - Salti, Nisreen; Chaaban, Jad; Irani, Alexandra; Al-Mokdad, Rima
Abstract: Background: Increasing refugee populations worldwide highlight the need for development indicators that cover refugees, especially as they tend to be excluded from national statistics. Refugee youth face double exclusion, as most wellbeing indices are not youth-specific. We developed a youth wellbeing index (YWI) for Palestinian refugees in Lebanon (PRL) and Palestinian refugees from Syria (PRS) living in Lebanon, with the aim of providing a snapshot of youth wellbeing to inform evidence-based youth-specific development strategies. Methods: The YWI was developed and its data generated using information from the 2015 survey of PRL and PRS, which was approved by the American University of Beirut Institutional Review Board. The wellbeing of PRL (n=3940) and PRS (n=1581) aged 15–29 was measured using the YWI, which examines five wellbeing dimensions: educational attainment, health, housing, active education or employment, and access to information. Scores for each of the five dimensions are scaled to [0, 1], and YWI is their arithmetic mean. The data enable us to look at the YWI by gender, by camp residence, and by narrower age bands to detect any generational differences within youth. Findings are reported using sampling weights for representativeness. Findings: 4 years after displacement (2011–2015), PRS youth showed lower levels of wellbeing (YWI=0·56, 95% CI 0·55–0·57) than PRL youth (YWI=0·65, 95% CI 0·64–0·67). Although money-metric poverty was significantly higher inside than outside camps for both PRL youth (inside camps, 75·00%, 95% CI 71·55–78·15; outside camps, 61·98%, 55·26–68·27) and PRS youth (inside camps, 93·89%, 90·56–96·1; ; outside camps, 88·72%, 85·35–91·39), there was no such disparity in the YWI for PRL youth (inside camps, YWI=0·65, 95% CI 0·63–0·66; outside camps, 0·66, 0·62–0·69) or PRS youth (inside camps, 0·55, 0·54–0·56; outside camps, 0·57, 0·54–0·59). Young male refugees had significantly higher YWI (PRL, 0·66, 95% CI 0·65–0·68; PRS, 0·57, 0·56–0·59) than young female refugees (PRL, 0·64, 0·62–0·66; PRS, 0·55, 0·53–0·56). Young female PRL and PRS scored significantly higher for education (PRL, YWI=0·60; PRS, 0·61) than young male refugees from these populations (PRL, 0·48; PRS, 0·47), but significantly lower on active education or employment (PRL, 0·45; PRS, 0·18) than the young male refugees (PRL, 0·72; PRS, 0·47). Older PRS scored higher on the YWI education dimension (20–24 years age group, 0·61; 25–29 years age group, 0·50) than their PRL peers (20–24 years age group, 0·53; 25–29 years age group, 0·45), but the reverse was true for the 15–19 years age group (PRL, 0·60; PRS, 0·53). Interpretation: Residence inside versus outside camps showed no significant differences in wellbeing based on the YWI, whereas money-metric poverty was higher inside camps, which suggests a need to move beyond assistance policies based on money-metric measures alone. The female edge in educational attainment is reversed when considering active education or employment, signalling the need for gender-specific strategies for the school-to-work transition for both PRL and PRS. The reversal of the educational edge of PRS over PRL in the 15–19 years age group is another concerning indicator of the cost of conflict for PRS that persists even four years after their displacement. Funding: UNRWA funded the 2015 survey data collection and the Economic Research Forum funded the development of the YWI.